Do anthropometrics, biomechanics, and laterality explain V1 side preference in skiers? - Stöggl, T.; Hébert-Losier, K.; Holmberg, H. C. (Medicine & Science in Sports & Exercise, 2013)
Purpose: In cross-country (XC) skiing, the V1 and V2 alternate skate techniques are asymmetric, and skiers can choose either the right or left side for pole support. The overall purpose of this study was to investigate V1 side preference in elite XC skiers, notably by documenting V1 skate side preference, dominant and nondominant V1peak speeds, left- to right-side differences (?L-R) in laboratory-based measurements, and relationships between side preference data.